Can We Infer Inter-Individual Differences in Risk-Taking From Behavioral Tasks? - Palminteri, Stefano; Chevallier, Coralie (Frontiers in Psychology, 2018)
Investigating the bases of inter-individual differences in risk-taking is necessary to refine our cognitive and neural models of decision-making and to ultimately counter risky behaviours in real-life policy settings. However, recent evidence suggests that behavioural tasks fare poorly compared to standard questionnaires to measure individual differences in risk-taking. Crucially, using model-based measures of risk taking does not seem to improve reliability. Here we put forward two possible - not mutually exclusive - explanations for these results and suggest future avenues of research to improve the assessment of inter-individual differences in risk-taking by combining repeated online testing and mechanistic computational models.